Postprocedural delirium following mechanical thrombectomy for acute ischemic stroke: a retrospective study - Sachdev, Alisha; Torrez, Daniel; Sun, Sarah; Michapoulos, George; Rigler, Nicholas C.; Feldner, Alexandra L.; Hong, Young Soo; McCarthy, Robert J. (Frontiers in Anesthesiology, 2024)
Introduction National representative estimates on in-hospital delirium after acute ischemic stroke are not well established and there is limited data on the impact of delirium on clinical outcomes following mechanical thrombectomy. We evaluated risk factors for delirium and the impact on outcomes following mechanical thrombectomy for acute ischemic stroke. Methods This is a retrospective study of patients who underwent mechanical thrombectomy for acute ischemic stroke at a single tertiary comprehensive stroke center between April 2011 and December 2019. Delirium was assessed using the Confusion Assessment Method for the Intensive Care Unit. Patient characteristics, comorbidities, laboratory data, elapsed times, tissue plasminogen activator use, duration of the procedure, type of anesthesia, National Institute of Health stroke scores (NIHSS), sedation scores, reperfusion grades, complications, length of hospital stay, discharge disposition, and 90-day mortality were evaluated. Results Five hundred and two patients were evaluated, and post-procedural delirium was identified in 24/467 (5.1%) patients. Thirty-five patients could not be assessed for delirium due to excessive sedation. The incidence of delirium in white vs. non-white patients <65 years was 5/137 (3.6%) compared to 0/91 (0%), and 7/176 (4.0%) compared to 12/63 (19%) in patients ≥65 years, P = 0.006. Bias reduction multi-variable analysis identified low postprocedural hemoglobin level odds ratio of 0.76 (95% CI 0.61–0.92, P = 0.006), greater age (odds ratio 1.04, 95% CI 1.01–1.009, P = 0.024), and non-white race odds ratio of 2.52 (95% CI 1.06–6.38, P = 0.030) as factors associated with delirium [Brier score = 0.045, C-index = 0.800, and Akaike Information Criterion (AIC) = 174]. General anesthesia was not associated with an increased delirium risk. NIHSS at 24 and 48 h and discharge, length of stay, and 90-day mortality were not different between delirium and no-delirium groups. Delirium patients had a reduced odds ratio of 0.13 (05% CI 0.01–1.00, P = 0.02) for home discharge. Discussion Delirium following mechanical thrombectomy for acute ischemic stroke primarily affected older patients and was associated with reduced odds of home discharge following hospitalization. Changes in NIHSS during hospitalization and 90-day mortality were not adversely affected by the presence of delirium. General anesthesia was not associated with an increased delirium risk following mechanical thrombectomy.